2016
DOI: 10.18172/cig.2935
|View full text |Cite
|
Sign up to set email alerts
|

The origin of glacial alpine landscape in Tröllaskagi Peninsula (North Iceland)

Abstract: ABSTRACT. The Tröllaskagi Peninsula is located in north central Iceland, between meridians 19º30'W and 18º10'W , limited

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…The final geomorphological map (Main Map) defines the most important units of the Hóladalsjökull debris-covered glacier and the Fremri-Grjótárdalur rock glaciers, and the internal features within each unit. The differentiation between active and relict rock glaciers agrees with criteria specified in previous publications (Andrés et al, 2016;Farbrot et al, 2007;Kellerer-Pirklbauer et al, 2008;Tanarro et al, 2019).…”
Section: Description Of Geomorphological Landformssupporting
confidence: 89%
See 2 more Smart Citations
“…The final geomorphological map (Main Map) defines the most important units of the Hóladalsjökull debris-covered glacier and the Fremri-Grjótárdalur rock glaciers, and the internal features within each unit. The differentiation between active and relict rock glaciers agrees with criteria specified in previous publications (Andrés et al, 2016;Farbrot et al, 2007;Kellerer-Pirklbauer et al, 2008;Tanarro et al, 2019).…”
Section: Description Of Geomorphological Landformssupporting
confidence: 89%
“…In the cirque-shaped headwaters of these valleys there are currently numerous glaciers, mostly not exceeding 2 km in length. A few are debris-free glaciers, and most are debris-covered and rock glaciers (Andrés, Palacios, Tanarro, & Fernández, 2016;Fernández, Andrés, Saemundsson, Brynjólfsson, & Palacios, 2017). Lilleøren et al (2013) have identified 118 rock glaciers, of which 51 are talus-derived rock glaciers and 67 are glacier-derived rock glaciers.…”
Section: Geographical Geological and Climatic Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…These cirques shelter over 160 small glaciers, mostly north-facing, resulting from the leeward accumulation of snow coming from the plateau (Caseldine and Stötter, 1993) and reduced exposure to solar radiation. Most of them are rock glaciers and debriscovered glaciers, due to the intense paraglacial activity affecting the walls (Andrés et al, 2016). These glaciers are characterized by almost static behaviour because the insulating effect of their debris cover leaves them with little or no sensitivity to the climate (Martin et al, 1991).…”
Section: Area Of Applicationmentioning
confidence: 99%
“…This article integrates a methodological sequence that complements most of the indicators and techniques presented in order to analyze the impact of climate change on glaciers and their response based on the analysis of different variables. Therefore, the objective of this study is to propose and evaluate a methodological approach applied in a particularly sensitive area where glaciers dynamically respond to the changes in the elements that make up the climate (Andrés et al, 2016), and applicable in any area of study. To illustrate the methodology, three glaciers have been selected (Gljúfurárjökull and Western/Eastern Tungnahryggsjökull) which are located in the interior of the Tröllaskagi Peninsula (northern Iceland).…”
Section: Introductionmentioning
confidence: 99%